Adolescent Running Biomechanics - Implications for Injury Prevention and Rehabilitation - McSweeney, Simon C.; Grävare Silbernagel, Karin; Gruber, Allison H.; Heiderscheit, Bryan C.; Krabak, Brian J.; Rauh, Mitchell J.; Tenforde, Adam S.; Wearing, Scott C.; Zech, Astrid; Hollander, Karsten (Frontiers in Sports and Active Living, 2021)
Global participation in running continues to increase, especially amongst adolescents. Consequently, the number of running-related injuries (RRI) in adolescents is rising. Emerging evidence now suggests that overuse type injuries involving growing bone (e.g., bone stress injuries) and soft tissues (e.g., tendinopathies) predominate in adolescents that participate in running-related sports. Associations between running biomechanics and overuse injuries have been widely studied in adults, however, relatively little research has comparatively targeted running biomechanics in adolescents. Moreover, available literature on injury prevention and rehabilitation for adolescent runners is limited, and there is a tendency to generalize adult literature to adolescent populations despite pertinent considerations regarding growth-related changes unique to these athletes. This perspective article provides commentary and expert opinion surrounding the state of knowledge and future directions for research in adolescent running biomechanics, injury prevention and supplemental training.